Adult-Onset Syringomyelia in Dandy-Walker Malformation Patients: Clinical Insights and Literature Review - Bojana Zivkovic; Mirko Micovic; Marko Todorovic; Jelena Kostic; Vladimir Bascarevic (Brain Sciences)
Introduction: The presence of syringomyelia associated with Dandy-Walker malformation is rarely described in adults. Case report: We report a case of a 28-year-old woman with a history of Dandy-Walker malformation who developed syringomyelia. She had been previously treated in childhood with a ventriculoperitoneal and cystoperitoneal shunt for hydrocephalus, but over time she developed progressive neurological symptoms, including numbness and weakness in the upper extremities. Magnetic resonance imaging revealed a syrinx extending from C4 to T1 associated with large posterior fossa cyst. The patient was treated with cyst fenestration and cystoperitoneal shunts were removed, with complete resolution of symptoms and disappearance of syrinx. Discussion: A literature review revealed only 6 cases of syringomyelia associated with Dandy-Walker malformation in adults. The pathophysiology of this entity is multifactorial and may be related to obstructed cerebrospinal fluid flow, altered pressure dynamics, and formation of arachnoid adhesions. Conclusions: Individualized surgical approaches are essential for optimizing outcomes in this rare condition. Further research is needed to standardize treatment protocols and clarify underlying mechanisms and help to improve the management of these patients.